Enhancing MSMEs productivity through e-commerce in Citromanggisan Village, Magelang District - Laili Qomariyah; Prayogo Agus Kuncoro; Afifudin Isnain; Anas Adha Saputra; Farica Ayu Nabila; Sofiyyatuw Wakhidah (Universitas Muhammadiyah Magelang, 2022)
Efforts to increase the productivity of MSMEs have not become a special agenda for village officials in Citromanggisan Hamlet. Therefore, the purpose of this community service is to help SMEs in increasing their productivity by increasing their knowledge and skills regarding e-commerce. This program is carried out using training and mentoring methods. The result of this program is that MSME actors have gained new knowledge about the entrepreneurial mindset, skills in making flyers through Canva, taking photos of business products independently, and being able to find value in their products.